Long-term outcome of endoscopic resection of superficial adenocarcinoma of the esophagogastric junction - Yamada, Masayoshi; Oda, Ichiro; Nonaka, Satoru; Suzuki, Haruhisha; Yoshinaga, Shigetaka; Taniguchi, Hirokazu; Sekine, Shigeki; Kushima, Ryoji; Saito, Yutaka; Gotoda, Takuji (Endoscopy, 2013)
Background and study aim: Endoscopic resection has been favored for the management of intramucosal adenocarcinoma of the esophagogastric junction (AEGJ) over standard treatment with surgical resection. Several previous studies have reported only short-term outcomes. The aim of the present study was to report the long-term follow-up and outcomes of endoscopic submucosal dissection (ESD), a representative endoscopic resection method, for the management of superficial AEGJ.Patients and methods: A retrospective cohort study included 53 consecutive patients with superficial AEGJ who underwent ESD between 2001 and 2007 at the National Cancer Center Hospital, Tokyo, Japan. Rates of overall survival, recurrence-free survival, and cause-specific survival of patients with AEGJ after endoscopic resection were analyzed.Results: The 5-year overall, recurrence-free, and cause-specific survival rates in the 53 patients were 94.2 %, 92.3 % and 96.1 %, respectively. The median follow-up was 6.1 years. En bloc, R0, and curative resection rates were 100 %, 79 %, 68 %, respectively. In 36 patients with curative resection, the cause-specific survival rate was 100 % and no recurrence or metastases were detected. In 17 patients with non-curative resection, recurrence was found in three patients (17 %); two of the three patients died of their disease whilst one patient received chemotherapy.Conclusions: Superficial AEGJ can be well controlled by ESD when curative resection is achieved.